PENENTUAN KOEFISIEN AIR LARIAN PADA SISTEM DRAINASE DI KOTA KEDIRI - Okik Hendriyanto (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2007)
Land use change in an area results in the change of soil infiltration rate. The impact which is possible to happen is flood. Change of land use will change the run off coefficient (C). This research is aimed to measure the run off coefficient in order to determine decreasing flood rate in Kediri City using flow rate data from rainfall analysis from river flow data. In this research 3 rain stations located in Kediri City were observed. Independent variables included drainage basin, rainfall, and river flow. Run off coefficient (C) was used as a dependent variable. Results of this research showed that the Jetting (Direct Run Off) Coefficient was 0.11-0.13. This value was low, considering that during the dry season, the river water flow decreased significantly. The decrease of the river water flow was because of the uses for irrigation and for fulfilling other human needs. but moment of the rains happened floods because drainage channel stuffed up by garbage.